Analysis of Management Information System for Financial Data Management (Case Study XYZ Polytechnic) - Az Zahra Izaaz; Tubagus Khudri (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
The Technology-Organization-Environment (TOE) framework is used to evaluate the adoption of Management Information System (MIS) for financial data management and provide recommendations for optimizing MIS implementation in XYZ Polytechnic with three contexts: technology, organization and environment. The research method uses a qualitative approach obtained from interviews with five respondents. The results showed that in the context of technology, the relative advantage attribute of MIS is useful in providing financial service information to all parties of XYZ Polytechnic, but in compatibility and complexity there are still technical obstacles in SIM, it needs improvement in the calculation of the Basic Teaching Fee accurately, employee pay slips with automatic format, actual data and information integration. For the organizational context, there needs top management support to make decisions in determining developers as MIS providers to fix these technical problems, sufficient training to improve the quality of human resources and additional MIS user staff for work efficiency according to organizational needs. Environmental factors are influenced by regulatory support in the form of Government Regulations and standard operating procedures to ensure the implementation and provision of MIS, industry characteristics with competition among colleges can improve Polytechnic performance through improving the quality of financial services on MIS.